RELATIONSHIP OF INDIVIDUAL CHARACTERISTICS, PHYSICAL HOME ENVIRONMENT AND BEHAVIOR WITH THE INCIDENCE OF PULMONARY TB IN CIJORO PASIR VILLAGE, MUARA VILLAGE EAST CIUJUNG AND WEST RANGKASBITUNG VILLAGE, RANGKASBITUNG SUBDISTRICT, LEBAK REGENCY 2019 - Rojali, Rojali; Sari, Dwita Indah (ADI Journal on Recent Innovation, 2020)
This study entitled "Relationship of Individual Characteristics, Physical Environment of the House and Behavior with the incidence of pulmonary TB in Cijoro Pasir Village, Muara Ciujung Timur Village and Rangkasbitung Barat Village, Rangkasbitung District, Lebak Regency in 2019" and behavior with pulmonary TB incidence. The design of this study was cross sectional. Data was analyzed using univariate tests and bivariate tests consisting of chi-square. The total population is 123 The results showed that the incidence of pulmonary TB as many as 37 patients with positive pulmonary TB (60.7%) and 24 patients with negative AFB pulmonary TB and still found a physical environment that did not meet the requirements as many as 42 houses (68.9%), lighting as many as 38 houses (63.3%), humidity of 43 houses (70.5%), BCG immunization 35 people (57.4%), closing mouths of cough / sneezing compilation 38 people (62.3%), phlegm carelessly 32 people (52.5%) and use of eating utensils 39 people (63.9%).